2013
DOI: 10.1128/aac.01032-13
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between the EUCAST Procedure and the Etest for Determination of the Susceptibility of Candida Species Isolates to Micafungin

Abstract: e We compared the ability of the EUCAST EDef 7.2 and the Etest to detect the susceptibility to micafungin of 160 Candida and non-Candida clinical isolates. Agreement was higher when Etest MICs were obtained after 24 h of incubation; essential agreement was 90%, and categorical agreement was >90%. False susceptibility was seen only for Candida krusei (10%), and false resistance was observed in 6% of the isolates, ranging from 2.6% (C. glabrata) to 13% (C. albicans).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Similarly, in another study, a comparison between Etest and CLSI methods showed an overall essential agreement of 94.7% and a categorical agreement of 97.2% (20). The ability of the Etest to detect micafungin resistance, for most of the species, has also been demonstrated previously by testing FKS mutant isolates (17,21,22). We enrolled 16 centers and demonstrated that the Etest gave micafungin susceptibility results that were very similar to those given by the EUCAST reference method under real-life conditions.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly, in another study, a comparison between Etest and CLSI methods showed an overall essential agreement of 94.7% and a categorical agreement of 97.2% (20). The ability of the Etest to detect micafungin resistance, for most of the species, has also been demonstrated previously by testing FKS mutant isolates (17,21,22). We enrolled 16 centers and demonstrated that the Etest gave micafungin susceptibility results that were very similar to those given by the EUCAST reference method under real-life conditions.…”
mentioning
confidence: 77%
“…(17)(18)(19)(20)(21)(22), but only a few comparative studies with a reference method have been performed (17,(20)(21)(22). In one of those previous studies, MarcosZambrano et al (21) tested 160 yeast isolates with both the Etest and EUCAST methods and reported an essential agreement of 90.3% at Ϯ2 log 2 dilutions (85.8% at Ϯ1 log 2 dilutions) and categorical agreement of Ͼ90%. Similarly, in another study, a comparison between Etest and CLSI methods showed an overall essential agreement of 94.7% and a categorical agreement of 97.2% (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We studied 5 previously reported fks mutant Candida isolates (Candida albicans, n ϭ 1; Candida glabrata, n ϭ 1; Candida tropicalis, n ϭ 3) (15,16) (Table 1) and 10 wild-type Candida species isolates, 2 for each fks mutant isolate, matching the biofilm profile and species of the mutant isolates (C. albicans, n ϭ 2; C. glabrata, n ϭ 2; C. tropicalis, n ϭ 6). In addition, we analyzed 12 intrinsically echinocandinresistant non-Candida species (Rhodotorula mucilaginosa, n ϭ 7; Tricho-sporon asahii, n ϭ 2; Trichosporon japonicum, n ϭ 1; Trichosporon dermatis, n ϭ 1; Arxula adeninivorans, n ϭ 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we analyzed 12 intrinsically echinocandinresistant non-Candida species (Rhodotorula mucilaginosa, n ϭ 7; Tricho-sporon asahii, n ϭ 2; Trichosporon japonicum, n ϭ 1; Trichosporon dermatis, n ϭ 1; Arxula adeninivorans, n ϭ 1). All isolates were obtained from positive blood cultures of patients with fungemia and were identified using the ID 32C system (bioMérieux, Marcy l'Etoile, France) and confirmed by amplification and sequencing of the ITS1-5.8S-ITS2 region (15,16).…”
Section: Methodsmentioning
confidence: 99%